Strong magnetoelastic effect in CeCo 1-xFexSi as Néel order is suppressed - Correa, V. F; Villagrán Asiares, A. G.; Betancourth, D.; Encina, S.; Pedrazzini, P.; Cornaglia, P.S.; García D.J.; Sereni, J. G.; Maiorov, B; Caroca-Canales, N; Geibel, Ch.; Sereni, Julián; et al. (American Physical Society, 2019)
Fil: Correa, V. F. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina